Evaluate and Intervene in Sensory Processing Disorders by Occupational Therapists in Early Intervention Teams of the North of Portugal - Araújo, Aline Patriota; Pereira, Ana Paula da Silva; Reis, Helena I.S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Background: The National Early Childhood Intervention System of Portugal is an organized set of services under the responsibility of the Ministries of Health, Labor, and Social Security and Education aimed to support children between 0 and 6 years old and their families, and its mission is to ensure Early Childhood Intervention. At present, there is no research to support the extent of the use of sensory interventions in early intervention teams of Portugal. Aims: This study aims to analyze and understand the role of occupational therapists who support children with Sensory Processing Dysfunction and their families in local Early Intervention Teams. Methods: A qualitative and descriptive research was developed using semi-structured interviews. The interviews were conducted with ten occupational therapists who have worked in Early Intervention Teams in the North of Portugal for at least one year. Results: Modulation and Praxis were the categories of Sensory Processing Dysfunction most identified. Families consider that Sensory Processing Dysfunctions interfere with children's performance in activities of daily living and playing. Early childhood educators report that Sensory Processing Dysfunctions influence the child's participation in food, playing, and in more structured and directed activities. To transfer skills, occupational therapists organize training for professionals, families, and early childhood educators. Conclusion: The importance of collaborative work between professionals and the child's family is evident, and the support they provide in the natural environment and daily routines.